Understanding and predicting the geographic distributions of phlebotomine sand flies in and around Europe - Danyang Wang; Anouschka R. Hof; Kevin D. Matson; Frank van Langevelde; Vít Dvořák; Ognyan Mikov; Ivelina Katerinova; Simona Tchakarova; Maria Antoniou; Jorian Prudhomme; Denis Sereno; Baptiste Vergnes; et al. (Climatic Change, 2025)
Climate and land-use changes influence the transmission of vector-borne diseases by affecting the distribution and survival of disease vectors. Numerous diseases are transmitted by phlebotomine sand flies (Diptera: Psychodidae: Phlebotominae), including leishmaniasis. Several major sand fly-borne diseases are responsible for high global disease burdens and high socio-economic costs. In Europe, over 20 known sand fly vector species are largely confined to the Mediterranean Basin, yet records of sand fly presence further north increase. Global warming is predicted to drive the spread of sand flies to large areas of Europe in the 21th century, an effect likely to be exacerbated by anthropogenic factors. However, the constraints to the geographic distributions of sand flies are not well understood. This study aims to increase the understanding of the drivers of the geographic distributions of sand flies, using species distribution modelling to systematically test links between sand fly occurrences and climatic, land-use, lithological, biodiversity and human population variables in Europe and adjacent Mediterranean regions. We found that moisture is the most important environmental variable both in explaining and in predicting sand fly occurrences. The projected suitable habitats are larger than the current known sand fly distributions, and these habitats are expected to expand due to changes in climate and land-use.

The mycobiota of the sand fly Phlebotomus perniciosus : Involvement of yeast symbionts in uric acid metabolism - Elena Martin; Ilaria Varotto Boccazzi; Leone De Marco; Gioia Bongiorno; Matteo Montagna; Luciano Sacchi; Priscilla Mensah; Irene Ricci; Luigi Gradoni; Claudio Bandi; Sara Epis (Environmental Microbiology, 2018)
Summary The knowledge of the fungal mycobiota of arthropods, including the vectors of human and animal diseases, is still limited. Here, the mycobiota associated with the sand fly Phlebotomus perniciosus , the main vector of leishmaniasis in the western Mediterranean area, by a culture‐dependent approach (microbiological analyses and sequencing of the 26S rRNA gene), internal transcribed spacer (ITS) rRNA amplicon‐based next‐generation sequencing, fluorescence in situ hybridisation (FISH), and genome sequencing of the dominant yeast species was investigated. The dominant species was Meyerozyma guilliermondii , known for its biotechnological applications. The focus was on this yeast and its prevalence in adults, pupae and larvae of reared sand flies (overall prevalence: 57.5%) and of field‐collected individuals (overall prevalence: 9%) was investigated. Using whole‐mount FISH and microscopic examination, it was further showed that M. guilliermondii colonizes the midgut of females, males and larvae and the distal part of Malpighian tubules of female sand flies, suggesting a possible role in urate degradation. Finally, the sequencing and analysis of the genome of M. guilliermondii allowed predicting the complete uric acid degradation pathway, suggesting that the yeast could contribute to the removal of the excess of nitrogenous wastes after the blood meal of the insect host.

Epidemiological survey on Leishmania infection in red foxes (Vulpes vulpes) and hunting dogs sharing the same rural area in Southern Italy - Diego Piantedosi; Vincenzo Veneziano; Trentina Di Muccio; Valentina Foglia Manzillo; Eleonora Fiorentino; Aldo Scalone; Benedetto Neola; Francesca Di Prisco; Nicola D’Alessio; Luigi Gradoni; Gaetano Oliva; Marina Gramiccia (Acta Parasitologica, 2016)
Southern Italy, particularly Campania region, is an area where canine leishmaniasis (CanL) and zoonotic human visceral leishmaniasis (VL) are endemic. The red fox (